A Single-Layer Ultra-Wideband Dual-Channel Differential Phase Shifter Using Coupled Lines - Robab Kazemi; Zohreh Asadollahzadeh-Zia; Reza Masoumi (Iranian Journal of Electrical and Electronic Engineering, 2023)
In this work, a broadband dual-channel differential phase shifter is developed with a small phase deviation across a wide frequency range. The design consists of two main lines for 45° and 90° phase shifts, along with a reference line. A prototype is fabricated and measured to validate the performance of the design. Phase shifts of 45° ± 5° and 90° ± 5° over a frequency range of 1.26 GHz - 4 GHz (bandwidth of 104%) are achieved from the channels. The transmission losses of the three lines are less than 0.35 dB and the isolation between the adjacent ports is better than 20 dB. The area of this dual-channel differential phase shifter is  (14.7 mm × 66.15 mm), where is the guided wavelength at the center frequency.